5 terms

Perform the operation when f(x) = −3x∧1/3 + 4x∧1/2 and g(x) = 5x∧1/3 + 4x∧1/2:

f(x) + g(x)

f(x) + g(x)

-3x∧1/3 + 4x∧1/2 + 5x∧1/3 + 4x∧1/2

= 2x∧1/3 + 8x∧1/2

= 2x∧1/3 + 8x∧1/2

(f(x) and g(x) are same as above)

g(x) - f(x)

g(x) - f(x)

5x∧1/3 + 4x∧1/2 - (-3x∧1/3 + 4x∧1/2)

= 5x∧1/3 + 4x∧1/2 + 3x∧1/3 - 4x∧1/2

= 8x∧1/3

= 5x∧1/3 + 4x∧1/2 + 3x∧1/3 - 4x∧1/2

= 8x∧1/3

(f(x) and g(x) are same as above)

f(x) - g(x)

f(x) - g(x)

-3x∧1/3 + 4x∧1/2 - (5x∧1/3 + 4x∧1/2)

= -3x∧1/3 + 4x∧1/2 - 5x∧1/3 - 4x∧1/2

= -8x∧1/3

= -3x∧1/3 + 4x∧1/2 - 5x∧1/3 - 4x∧1/2

= -8x∧1/3

Perform indicated operation when f(x) = 2x² and

g(x) = 5x - 4:

f(x) × g(x)

g(x) = 5x - 4:

f(x) × g(x)

2x²(5x - 4)

= 10x³ - 8x²

= 10x³ - 8x²

When f(x) = 4x-3, g(x) = -x² and h(x) = x-5/2, find

f(g(2))

f(g(2))

g(2) = -(2)², g(2) = -4

f(-4) = 4(-4) - 3

= -16 - 3

= -19

f(-4) = 4(-4) - 3

= -16 - 3

= -19